2016
DOI: 10.1136/bcr-2016-216591
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomatosis cerebri: diagnostic challenges and review of the literature

Abstract: Lymphomatosis cerebri (LC) is a rare variant of a primary central nervous system non-Hodgkin's lymphoma (PCNSL) characterised by diffuse infiltration of tumour cells throughout the brain parenchyma. We present a 68-year-old immunocompetent woman with headaches, dizziness, blurred vision, localised right leg weakness and rapidly progressive dementia. A brain MRI demonstrated diffuse T2 hyperintense white matter lesions that did not enhance with contrast. The clinical differential diagnosis of these lesions incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…The MRI typical finding is non-contrast enhancing lesions involving predominantly white matter of both hemispheres, including in some cases supra-tentorial and infra-tentorial regions can be concurrent affected². The most common affected areas are both hemispheres and the basal ganglia1,3 .In accordance to the literature, the present patient had frontal, insular, temporal lobes and at thalamus and mesencephalus lesions.LC clinical presentation is quite variable, but, gait disturbance, cognitive decline and behavioral changes are the most common 2,3 . Our patient had two of the three main manifestations.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The MRI typical finding is non-contrast enhancing lesions involving predominantly white matter of both hemispheres, including in some cases supra-tentorial and infra-tentorial regions can be concurrent affected². The most common affected areas are both hemispheres and the basal ganglia1,3 .In accordance to the literature, the present patient had frontal, insular, temporal lobes and at thalamus and mesencephalus lesions.LC clinical presentation is quite variable, but, gait disturbance, cognitive decline and behavioral changes are the most common 2,3 . Our patient had two of the three main manifestations.…”
supporting
confidence: 89%
“…The prognosis of LC is poor, recent study evidenced a median overall survival of 2.95 month 3 . Multivariate analysis demonstrated that good clinical initial conditions and treatment with methotrexate were independent favorable survival prognostic factors 1,3 . The present patient was treated with methotrexate, vincristine and rituximabprocarbazine and nowadays patient has almost a full neurologic recovery, with just some visual symptoms, after two years of the onset.…”
Section: Case Reportmentioning
confidence: 98%
See 1 more Smart Citation
“…The unusual radiological finding, associated with clinical presentation of rapidly progressive dementia, opens a wide list of differential diagnosis that includes Creutzfeldt-Jakob disease; [5,6,18,25,41] infectious and inflammatory encephalitis; [4,5,16,19,21,24,25,41,4548] autoimmune encephalopathy; [22,36,38,47] hypertensive encephalopathy; [47] demyelinating diseases; [4,16,18,21,40,43,45] Binswanger disease (subcortical ischemic vascular dementia) [5,19] and other vascular disorders; [5,21,25] gliomatosis; [5,17,19,27,37,45,50] tumor metastases; [21] toxic and metabolic processes; [5,6,18,30,45] and neurodegenerative diseases. [6,40]…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were as follows: i) Concurrent systemic lymphoma; ii) intravascular CNS lymphoma; iii) inconclusive histological data; iv) failure to provide any MR image in the full-text article; v) only providing CT images in the full-text article; vi) prior surgery, radiotherapy, chemotherapy or corticosteroid therapy; and vii) a non-English article. Any case report that did not meet this definition and these criteria was excluded from the present systematic review, even if the author referred to the condition as lymphomatosis cerebri ( 6 11 ). The present study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines ( 12 ).…”
Section: Methodsmentioning
confidence: 99%